Goodfruits Sdn. Bhd. / Mohammad Masnoor Md Jahrin ... [et al.] - Md Jahrin, Mohammad Masnoor; Ali Yasak, Wahida; Ahad, Umi Natera; Mohd Zin, Nur Nirmala Indryati; A. Rahman, Norhafizah; Mahd. Zin, Noor Dalilah (Faculty of Communication and Media Studies, 2004)
We choose to run this business by considering these factors; First of all is Malays entrepreneur are very rarely involved in this business. It is because they do not see its potential. Only the Chinese interested in this kind of the business. This helps us to widen our business, because the consumer or buyers will be more confident and comfortable to buy our fruits especially the Malays and Muslims.